Development of Chitosan-Based Antimicrobial Hydrogel Incorporating Polyvinylpyrrolidone and PHMG - Ivanov, Ivan; Shatalov, Denis (Sciences of Pharmacy, 2024)
This study focuses on the development of a chitosan-based hydrogel incorporating polyvinylpyrrolidone and polyhexamethylene guanidine hydrochloride for the rehabilitation of damaged and contaminated skin. The thermal properties of chitosan-containing films were characterized by measuring the glass transition temperature (Tg) using differential scanning calorimetry. Due to challenges in accurately determining the Tg of chitosan from experimental and literature data, an additional method, dynamic mechanical analysis, was employed. Using the literature value for the Tg of polyhexamethylene guanidine hydrochloride, the transitions of the components were determined. The estimated sorption capacity of the developed hydrogel showed that the inclusion of polyhexamethylene guanidine hydrochloride reduced the moisture content, as expected. However, the overall behavior of the hydrogels remained similar. Vapor permeability, an important factor in wound healing, was also evaluated. Antimicrobial testing revealed no activity for the chitosan control sample despite some reports in the literature, while the samples containing polyhexamethylene guanidine hydrochloride exhibited superior antimicrobial efficacy. These findings suggest that the incorporation of polyhexamethylene guanidine hydrochloride and polyvinylpyrrolidone significantly enhances both the mechanical strength and antimicrobial potential of chitosan-based hydrogels, positioning them as promising candidates for the treatment of contaminated wounds.